Eco-Fashion Design Model Based on the Clothing Life Cycle - Marzie Hatef, Jalil (UNIMAS, 2020)
Eco-fashion clothes offer considerable promise to reduce clothing waste associated with improving consumer profits and the health of the community and extending the clothing life cycle. This research aims to develop an Eco-fashion design model based on the clothing life cycle. Therefore, the investigation of phases involved in the clothing life cycle is important. Subsequently, a capsule clothing collection named “Eco capsule wardrobe” was proposed in line with the life cycle concept. Therefore, this research seeks to discover phases related to the life cycle of clothing known as consumer, designer, design process and material to extend the clothing life cycle with supporting the three main pillars of Eco-fashion design: society, economy and the environment. Henceforth, the objectives of this research were; to explore consumer’s behaviour and designer’s behaviour on the decision toward Eco-fashion design subjects; to develop an Eco-fashion design model to source Eco-fashion materials and create Eco-fashion prototype, and finally to evaluate society’s perception to the Eco-fashion prototype. The environmental-social, environmental-economic, and social-economic aspects among consumer, designer, design process and used material in Eco-fashion design subject were discovered for more investigation. Given these gaps, the researcher sought to contribute to the existing knowledge on clothing life cycle that is the consumer’s behaviour, and designer’s behaviour, material sourcing and design process that shall improve the existing Eco-fashion design model. This study applied the Theory of Reasoned Action (TRA) and Theory of Planned Behaviour (TPB) as the foundation of the designer’s behaviour and consumer’s behaviour to discover the individuals’ behaviour, respectively. Also, a design experiment workshop for designing Eco capsule wardrobe with Eco-fashion materials was done for the design outputs evaluation by two focus-group discussion. Overall, the Eco-fashion design model showed that consumer’s and designer’s behaviour are influential factors in forming clothing design, especially on choosing the materials and design techniques, as well as to encourage sustainability in the fashion industry. Additionally, the Eco-fashion design model was used to making a profit and protecting the environment and people's health that can be achieved through investigation of the consumer’s behaviour, the discovery of the designer’s behaviour, exploration of the materials which are recyclable and finally study on the most related and easy to use Eco-fashion design techniques. So, this leads to design sustainability, where clothes can be disassembled and recycled easily after use and return to the economic system instead of burning. Hence, this model can help the designer and manufacture to identify the material and design techniques, therefore, the amount of unsafe material released into the planet and living place which is threatening health problem of current society could be reduced.